Pengaruh Religious Commitment Terhadap Penyesuaian Diri Mahasiswa - Halimatus Sakdiah; Rabiatul Afawiyah; Muhammad Husaini Abbas (Jurnal Studia Insania, 2018)
The self-adjustment ability on campus is an important requirement of studenteducation success. Therefore students should have good adjustment skills. This study aims to determine the adjustment ability and religious commitment of students in the campus IAIN Antasari, and to know the influence of religious commitment to student self-adjustment. The method used is quantitative method, with simple linear regression analysis. The research subjects were IAIN Antasari students in each faculty, and 236 students were selected as samples. The results showed that there was a significant positive religious commitment influence on the students' self adjustment at IAIN Antasari (R = 0.699 (r = 0.000)). Each dimension of religious commitment also has a significant positive effect on students' self-adjustment. The influence of religious belief dimension (R = 0.484 (r = 0.000)), religious practice dimension (R = 0.596 (r = 0.000)), religious knowledge dimension (R = 0.613 = 0.000)), and religious effect dimension (R = 0.689 (r = 0.000)) on students’ self-adjustment. It shows that the higher the religious commitment of the students, the better the students' self-adjustment. Therefore, the religious commitment of students is very important to be improved so that the students' self-adjustment will be better.